Cenozoic deformation and crustal shortening in the foreland of southern Tian Shan, NW China, as a response to the India-Asia collision. (1st October 2019) - Lü, Lixing; Sun, Jimin; Zhang, Zhiliang; Jia, Yingying; Li, Tao; Li, Chunhong; Tian, Shengchen; Cao, Mengmeng
Graphic abstract: Highlights: The study area is featured by three en echelon décollement folds. The shortening rates of the three anticlines range from 0.35 mm/yr to 0.77 mm/yr. Folds and strike-slip faults account for the crustal deformation in the study area. Episodic deformation has been a response to the ongoing India-Asia convergence. Abstract: Investigations of geometry and kinematics of foreland fold-and-thrust belts provide key information for understanding how convergence is accommodated in deformed forelands of orogenic belts. Here, we present the structural styles, deformation ages and shortening rates of three en echelon anticlines located at the west end of the Baicheng-Kuqa foreland fold-and-thrust belt. The results indicate that the three anticlines developed above the Eocene evaporites of the Kumugeliemu Group which constitute the décollement level in this typical thin-skinned tectonics. The initial growth of the East Awate and North Kalayuergun anticlines, as indicated by the syn-tectonic growth strata accumulations, occurred at ~5.3 Ma with shortening rates of ~0.70–0.77 mm/yr and ~0.40–0.43 mm/yr, respectively. Whereas, the initial folding time of the Middle Kalayuergun anticline is ~2.6–1.7 Ma, resulting in a shortening rate of ~0.35–0.65 mm/yr. The shortening rates are lower when compared with foreland deformation in the middle and eastern parts of the Baicheng-Kuqa fold-and-thrust belt. Such differences are mostly related to the strain partitioning caused by the NW-SE dextral strike-slip Kalayuergun fault as well as the influence of a dextral wrenching component in the west end of the Baicheng-Kuqa fold-and-thrust belt. Our study suggests that episodic tectonic deformation in the southern foreland of Tian Shan has been a response to the ongoing India-Asia convergence since the latest Miocene, and the spatial variability of crustal shortening rates has depended on regional tectonic differences.